A single nucleotide polymorphism rs553668 in the ADRA2A gene and the status of Polish elite endurance athletes - Sawczuk, Marek; Maciejewska-Karłowska, Agnieszka; Cięszczyk, Paweł (Akademia Wychowania Fizycznego w Poznaniu)
The variance in human athletic ability is the result of interaction of both genetic and environmental factors. The ADRA2A gene that encodes adrenergic receptors α2 is likely to be a candidate gene because ADRA2A receptors are crucial for precise cardiovascular control and are involved in the regulation of adipocyte lipolysis, glucose metabolism and insulin secretion. Several genetic variants of the ADRA2A gene have been identified, and one nucleotide polymorphism (SNP) rs553668 seems to be of special importance. On the basis of results of available studies it is assumed that the C allele of rs553668 might be associated with the status of Polish elite endurance athletes. Aim of the Study. The purposes of the study were to determine the distribution of the ADRA2A rs553668 SNP genotypes within a sample of Polish elite endurance athletes and sedentary controls to investigate a possible association between genetic polymorphisms in the ADRA2A gene and elite endurance athlete status and to check for an association between the rs553668 genotypes and alleles and the athlete status. Material and Methods. The study was performed on a group of 123 elite Polish endurance-oriented athletes. Control samples were prepared from 228 unrelated, sedentary volunteers. Results. No statistical differences were found between the endurance athletes and the control group across the ADRA2A C/T genotypes. Similarly, no statistical differences among the subgroups of top-elite, elite and sub-elite endurance athletes were observed. Conclusions. We found that the C allele as well as C-containing genotypes were not significantly more frequent in endurance athletes than in controls. This may suggest that harboring the T allele of the SNP rs553668 allele does not decrease the probability of being an endurance-oriented athlete in the Polish population. In respect to the analyzed population of Polish endurance athletes the ADRA2A gene can not be considered a candidate determinant of individual variations in exercise-related phenotypes.
Keywords: ADRA2A gene; rs553668; polymorphism, genetic; elite athletes